Unpacked Cases: Migratory Aesthetics as a Mode of Participation and Agency - Moise, Gabriella (Hungarian Journal of English and American Studies, 2021)
The manifold notion of migratory aesthetics serves as the critical grounding for this analysis focusing on Mohamad Hafez’s and Ahmed Badr’s multimedia installation, UNPACKED: Refugee Baggage (2017-2020), a socially and politically committed artistic project. Migratory aesthetics as a conceptual frame can encompass artifacts reflecting upon the experience of forced migration, displacement, and uprootedness. However, the concept also proposes the engendering of a platform for the confluence of art and the political. In accordance with the theories of Mieke Bal, Miguel Á. Hernández-Navarro, and Jacques Rancière, “political” is meant to signify a space of generative conflict, an active, communal, participatory encounter between sentient bodies and artworks. UNPACKED confronts the audience on many levels: physically, by leaving them in limbo, suspended between the inside and the outside, the private and the public, safety and threat; conceptually (owing to the phenomenal, embodied experience of the viewers), by provoking a sense of dislocation and homelessness, resulting in the potential for identification with the status of being a refugee, a migrant, and an asylum seeker. UNPACKED encapsulates, both spatially and temporally, the invisible and silenced trauma of forced migration, eventually effectuating collective understanding in the constitutive political space of art. (GM)